Fabrication of superoleophobic cotton fabric for multi-purpose applications. (10th June 2019) - Tudu, Balraj K.; Kumar, Aditya; Bhushan, Bharat
Abstract : Superoleophobicity is of interest for practical applications such as liquid repellency, self-cleaning, stain resistance, anti-bacterial properties and oil–water separation. In this work, the superoleophobic coating on cotton fabric was applied by simple immersion in TiO2 nanoparticles, perfluorodecyltriethoxysilane and tertraethylorthosilicate solution. Its anti-wetting properties, surface morphology and functionality were characterized. The coated cotton fabric shows superoleophobicity with oil (surface tension more than 27 mN m −1 ) contact angle of 152° and tilt angle of 6°. Furthermore, the superoleophobic cotton fabric was demonstrated to exhibit self-cleaning, stain resistance, mechanical durability, chemical stability, thermal stability, anti-bacterial properties and oil–water separation capabilities. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 2)'.